Mirror symmetry for orbifold del Pezzo surfaces - Cavey, Daniel (2020)
Mirror symmetry evokes a correspondence between deformation equivalence classes of toric varieties and mutation equivalence classes of the corresponding Fano varieties. This thesis discusses many computations and examples of this ilk, in the case when the varieties are 2-dimensional and permitted to possess cyclic quotient singularities.